Cross-Cultural Analysis of Volition: Action Orientation Is Associated With Less Anxious Motive Enactment and Greater Well-Being in Germany, New Zealand, and Bangladesh - Chatterjee, Monischa B.; Baumann, Nicola; Osborne, Danny; Mahmud, Shamsul H.; Koole, Sander L. (Frontiers in Psychology, 2018)
Background: People differ in action versus state orientation, that is, in the capacity for volitional action control. Prior research has shown that people who are action- rather than state-oriented are better able to perceive and satisfy own motives (e.g., affiliation, achievement, power), which translates into greater psychological well-being (Baumann, Kaschel, & Kuhl, 2005; Baumann & Quirin, 2006). However, most of the extant literature has been limited to samples from European countries or the US. To address this shortcoming, the present paper investigated the associations between action versus state orientation, psychological well-being, and anxious style of motive enactment among samples in Germany, New Zealand, and Bangladesh (combined N = 862). Methods: To examine the consistency of our results across countries, a multi-group structural equation model (SEM) was used to examine the associations between action orientation, anxious motive enactment, and well-being. Subsequent mediation analyses assessed whether anxious motive enactment mediated the relationship between action orientation and well-being across each of the three samples. Results: Across all three cultural groups, action orientation was associated with less anxious motive enactment and higher well-being. Moreover, mediation analyses revealed significant indirect paths from action orientation through less anxious motive enactment to well-being that were similar across the three samples. Conclusions: These findings suggest that individual differences in action versus state orientation have a similar psychological meaning across Western and non-Western cultures.